Obligatory and Property Contracts: Academic Chic or Intellectual Luxury? - Vavzhenchuk, Sergiy (Problems of legality, 2025)
The article is devoted to clarifying the peculiarities of the model of obligatory and property contracts. The study of the legal model of property and obligatory contracts is primarily driven by the rapid reform processes of recodification of Ukraine’s civil legislation. After all, the contract law of Ukraine requires the introduction of high-quality and balanced legal structures that will improve property circulation without excessive burden. The focus on obligatory and property contracts is driven by the convergence of private law in Ukraine and the EU, with Germany at the center. Consideration of this issue is impossible without reference to the contract law of Germany, since it is there that this legal model was born and polished. In order to decide whether it is expedient to introduce the model of obligatory and property contracts, first of all, it is necessary to clarify the legal nature of such contracts and the doctrinal approaches which serve as the methodological basis in this vector of scientific research. The purpose of the article is to elucidate, based on the doctrine of contract law, the peculiarities of the construction of obligatory and property contracts. In terms of methodology, the article is based on the analysis of German doctrine, national opinions and legislation covering the doctrine of obligatory and property contracts. The study is based on the following general and special methods of scientific and legal cognition: formal logical, generalization, linguistic analysis, and comparative legal method. The formal-logical method is manifested in the study of diffusions of legal regulation. The study of foreign doctrine and individual points of view of foreign lawyers regarding the understanding of obligatory and property contracts was carried out using the method of generalization and linguistic analysis. The comparative legal method made it possible to compare the approaches to the understanding of obligatory and property contracts existing in the German doctrine and in the national contract law science and to analyze the prospects for legitimizing the legal model of obligatory and property contracts in national contract law. These methods make it possible to objectively and fully outline the main features of the legal model of obligatory and property contracts contracts. According to the results of the study, legitimization of the aforementioned contractual model will require changing the structure of regulation of relations on transfer of property and fixing a closed list of property rights at the level of certain provisions of the Civil Code of Ukraine, as well as changing the model of implementation of such a remedy as invalidation of a transaction.